The effect of nanometre-scale V-pits on electronic and optical properties and efficiency droop of GaN-based green light-emitting diodes - Shengjun Zhou (Nature Portfolio, 2018)
Abstract The development of efficient green light-emitting diodes (LEDs) is of paramount importance for the realization of colour-mixing white LEDs with a high luminous efficiency. While the insertion of an InGaN/GaN superlattice (SL) with a lower In content before the growth of InGaN/GaN multiple quantum wells (MQWs) is known to increase the efficiency of LEDs, the actual mechanism is still debated. We therefore conduct a systematic study and investigate the different mechanisms for this system. Through cathodoluminescence and Raman measurements, we clearly demonstrate that the potential barrier formed by the V-pit during the low-temperature growth of an InGaN/GaN SL dramatically increases the internal quantum efficiency (IQE) of InGaN quantum wells (QWs) by suppressing non-radiative recombination at threading dislocations (TDs). We find that the V-pit potential barrier height depends on the V-pit diameter, which plays an important role in determining the quantum efficiency, forward voltage and efficiency droop of green LEDs. Furthermore, our study reveals that the low-temperature GaN can act as an alternative to an InGaN/GaN SL structure for promoting the formation of V-pits. Our findings suggest the potential of implementing optimized V-pits embedded in an InGaN/GaN SL or low-temperature GaN structure as a beneficial underlying layer for the realization of highly efficient green LEDs.